PROSES KERJA MASYARAKAT NELAYAN: Studi Kasus Nelayan Patorani di Desa Pa’lalakkang Kecamatan Galesong Utara Kabupaten Takalar Provinsi Sulawesi Selatan - Talitha Wenifrida (Journal Agriculture Sciences, 2017)
This research is motivated by the perspective to think that the cause of the lack of success of the government in an effort to increase the income and standard of living of fishermen is the lack of attention to social and cultural aspects of fishing communities. Therefore, this study was conducted to obtain social information alligator fishing communities that can be used to assist the government in improving the income and living standards of fishermen. This study aims to determine the fishing community work process from preparation Patorani fishing, production processes, marketing system until the system of rewards / profit sharing. The study found that the typical behavior of fishermen Patorani the work is to implement two kinds of traditional knowledge, namely ErangPassimombalang (knowledge cruise) and ErangPakboya-Boyang (knowledge of business organization). While Patorani work process, starting from (1) the preparation of the arrest, which perform rituals Patorani namely massikkopakkaja, massisibiseang and accaru-caru.It’s implementation has been simplified with the aim of saving operating costs, without reducing the significance of ceremonial purposes, namely for safety and success in work. (2) poses production, conducted in the East, is located in the Makassar Strait. Fishing gear used, namely traditional still pakkaja and balla-balla. (3) The marketing system is the right papalele, without the intervention of the skipper, the marketing system, from papalele to traders or exporters, while (4) the sharing system, determined by papalele. The reward system is not put in question by labor (skipper and mustard greens) because there is no guarantee unwritten papalele to provide social and economic security against the skipper and mustard during their work on the papalele. The conclusion that can be drawn from this research is: the process of working fishermen Patorani, still use traditional ways, by maintaining the socio-cultural aspects (indigenous) community.